2018
DOI: 10.1186/s12302-018-0154-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different wastewater treatment technologies on genotoxicity and dioxin-like toxicity in effluent-exposed fish

Abstract: Background: In situ exposure of rainbow trout up-and downstream of differently equipped wastewater treatment plants (WWTPs) and subsequent analyses of micronuclei frequencies and hepatic EROD activities were used to evaluate the impact of the effluents on fish health. Two of the facilities (WWTPs A and B) were conventional treatment plants. WWTP C has been equipped with a powdered activated carbon stage. Here, analyses were conducted prior and subsequent to this upgrade. Results:Differences did not only occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
0
8
1
Order By: Relevance
“…This project aimed to survey the efficiency of advanced wastewater treatment for (1) the reduction in micropollutants and bacteria in the effluent and (2) the possible improvement in wildlife health in WWTP-connected rivers. To the best of our knowledge, SchussenAktivplus is the first project worldwide that has addressed this topic using a holistic approach, simultaneously recording the Definition of sensitive taxa according to assessment procedures from Austria [56,57]. The assessment of the macrobenthos community is generally based on [58,59] presence, concentrations, and impact of chemical compounds and opportunistic pathogens, both in the effluent of the WWTP and in the connected river.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This project aimed to survey the efficiency of advanced wastewater treatment for (1) the reduction in micropollutants and bacteria in the effluent and (2) the possible improvement in wildlife health in WWTP-connected rivers. To the best of our knowledge, SchussenAktivplus is the first project worldwide that has addressed this topic using a holistic approach, simultaneously recording the Definition of sensitive taxa according to assessment procedures from Austria [56,57]. The assessment of the macrobenthos community is generally based on [58,59] presence, concentrations, and impact of chemical compounds and opportunistic pathogens, both in the effluent of the WWTP and in the connected river.…”
Section: Discussionmentioning
confidence: 99%
“…After the installation of the additional treatment with powdered activated carbon, these differences were no longer visible. In particular, a pronounced reduction in deleterious histopathological alterations in different organs [30], as well as a reduction in genotoxic (micronuclei) and dioxin-like (EROD activity) effects [26,32,56], could be detected in fish exposed downstream of the effluent after the WWTP upgrade. Very similar observations were made in rainbow trout and brown trout exposed at the bypass station and in feral fish caught downstream of the WWTP.…”
Section: Fish Healthmentioning
confidence: 99%
“…Evidence from both field and laboratory studies have shown a clear link between exposures to WwTW effluents and adverse health effects in aquatic wildlife. In fish, these effects include altered reproductive development (Tetreault et al, 2012;Thorpe et al, 2009), genotoxic damage (Rocco et al, 2012;Wilhelm et al, 2018), alterations in immune function (Borgia et al, 2018;Liney et al, 2006), cytotoxic and oxidative damage (Gagné et al, 2006;Lacaze et al, 2017b), nephrotoxicity (Liney et al, 2006) and alterations in behaviour (Gauthier and Vijayan, 2020;McCallum et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, micropollutants are detected at concentrations in the ng to mg/L range in surface waters, which may elicit effects on aquatic organisms (Han Tran et al, 2018;Wilhelm et al, 2018;Ashauer, 2016;Malaj et al, 2014).…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%